The influence of water table fluctuation on hydrarch succession in two subarctic peatlands in Eastern James Bay, Quebec - Ferguson, Crystal (2018)
Northern peatlands contain close to one-third of the world’s soil carbon and changes to their ecology and hydrology play a major role in the fate of these carbon stocks and the direction of their climate feedbacks. Recent research has largely focused on modern controls on peatland development and only few studies have explored the long-term (millennial scale) synergies between peatland hydrology and ecological succession. In this study, I use two peat cores from eastern James Bay (Québec) to investigate the interaction between peatland ecology (hydrarch succession) and hydrology while considering both allogenic and autogenic drivers of peatland development. The James Bay region provides an ideal location for this study as the postglacial retreat of the vast Laurentide Ice Sheet has resulted in a unique land uplift phenomenon. This process is called glacio-isostatic rebound and has been ongoing for the last ~7000 years. One of the main consequences of glacio-isotatic uplift is rapid marine regression and the creation of a landscape gradient of increasing age (chronosequence), from the coastline to the interior, that features varying stages of peatland development. In my investigation, I use a suite of palaeoecological proxies (testate-amoeba, C/N ratios, and AMS carbon-14 chronostratigraphy) to reconstruct changes in peatland water table depth through time. This hydrological reconstruction was then compared to the reconstruction of wetland community change to determine how hydrology affects wetland successional changes (hydroseres) through time. My results indicate a nuanced role of hydrology in hydrarch succession ranging from substantial, at one site (OFL) to marginal, at the other (W55). My results further suggest that local factors (topography, drainage patterns, and local base levels) largely control peatland development in this region although large-scale drivers, such as climate and isostasy, have also played a role.